Internal Whistleblowing: Analysis of Personal Characteristics and Organizational Commitments with Ethical Climate as Moderating Variables - Harry Setiadi; Rita Anugerah; Yesi Mutia Basri (Politeknik Negeri Madiun, 2022)
The desire of individuals within an organization to be willing to take whistleblowing actions will be very beneficial for the organization to achieve its goals. However, the desire or intention to carry out internal whistleblowing is still low in practice. This can be caused by organizational commitment, Personal Cost, Machiavellian Character, and Ethical Climate. This study examines and analyzes the effect of organizational commitment, personal cost, and machiavellian character on the intention to carry out internal whistleblowing with an ethical climate as a moderating variable. This research was conducted using a survey method by distributing questionnaires to civil servants in the finance department of the Riau Provincial Government. The non-probability sampling technique does the sampling technique. Seventy-three questionnaires can be used. Data analysis using WarpPLS 7.0. The findings of this study suggest that the intention to engage in internal whistleblowing is influenced by organizational commitment, personal cost, and Machiavellian character. The influence of organizational commitment, personal cost, and machiavellian character on the intention to engage in internal whistleblowing can be moderated by the ethical context